2021
DOI: 10.1515/sjpain-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine effects on morphine analgesic tolerance in rats

Abstract: Objectives To alleviate different pain intensities, morphine administration has been extensively used. However, prolonged administration of morphine leads to a progressive decline of its analgesic effect which limits their overall utility. Morphine tolerance is considered as a challenging issue for the treatment of both acute and chronic pain. We conducted this study in rats to investigate the effect of paroxetine on morphine tolerance when used preemptively or after morphine tolerance had de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A recent study showed that citalopram delayed tolerance to morphine [ 58 ]. Paroxetine use after the onset of morphine tolerance reduces tolerance to morphine, but concomitant use with opioids may lead to the risk of accidental overdose [ 59 ]. Venlafaxine, on the other hand, reduces morphine-induced analgesic tolerance and naloxone-induced morphine withdrawal symptoms [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that citalopram delayed tolerance to morphine [ 58 ]. Paroxetine use after the onset of morphine tolerance reduces tolerance to morphine, but concomitant use with opioids may lead to the risk of accidental overdose [ 59 ]. Venlafaxine, on the other hand, reduces morphine-induced analgesic tolerance and naloxone-induced morphine withdrawal symptoms [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%